2007
DOI: 10.1002/mnfr.200600202
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gastric H+,K+‐ATPase and Helicobacter pylori growth by phenolic antioxidants of Zingiber officinale

Abstract: Ulcer is a common global problem characterized by acute gastric irritability, bleeding, etc. due to either increased gastric cell proton potassium ATPase activity (PPA) or perturbation of mucosal defence. Helicobacter pylori has been identified as a major ulcerogen in addition to oxidative stress and nonsteroidal anti-inflammatory drugs. In this paper, we report ginger-free phenolic (GRFP) and ginger hydrolysed phenolic (GRHP) fractions of ginger (Zingiber officinale) as potent inhibitors of PPA and H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 47 publications
3
74
0
1
Order By: Relevance
“…In fact, the cytoprotective and gastric anti-ulcer effect of ginger have been showed experimentally in early studies in rats (Yamahara et al, 1988;Wu et al, 1990). Recently, data provides evidence for the potential ulcer-preventive ability of phenolics in ginger aqueous extract and addresses the probable mode of action through the inhibition of gastric H + , K + -ATPase and Helicobacter pylori growth (Siddaraju et al, 2007;Nanjundaiah et al, 2009). Thus, ginger and many of its chemical constituents have been shown, in numerous experimental and clinical studies, to be useful in combating several health disturbances, providing evidences to explain the actions of folk medicines in terms of conventional biochemistry and pharmacology.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 99%
“…In fact, the cytoprotective and gastric anti-ulcer effect of ginger have been showed experimentally in early studies in rats (Yamahara et al, 1988;Wu et al, 1990). Recently, data provides evidence for the potential ulcer-preventive ability of phenolics in ginger aqueous extract and addresses the probable mode of action through the inhibition of gastric H + , K + -ATPase and Helicobacter pylori growth (Siddaraju et al, 2007;Nanjundaiah et al, 2009). Thus, ginger and many of its chemical constituents have been shown, in numerous experimental and clinical studies, to be useful in combating several health disturbances, providing evidences to explain the actions of folk medicines in terms of conventional biochemistry and pharmacology.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 99%
“…Determination of the phenolic content and antioxidant activity of SRPP Since phenolics are generally found to be associated with polysaccharides, we evaluated the phenolic content in SRPP using a Folin-Ciocalteu reagent as described previously [16] . Gallic acid was used as a standard for the generation of a calibration curve.…”
Section: Isolation Of Pectic Polysaccharide From Swallow Rootmentioning
confidence: 99%
“…Superoxide dismutase, ascorbic acid, glutathione and uric acid levels were reduced and xanthine oxidase, glutathione-s-transferase activities were increased in alcohol treated rats while these parameters came to normalcy in ethanolic extract of ginger treated rats demonstrating the antioxidant effect of ginger [44]. Siddaraju and Dharmesh [45] demonstrated that ginger-free phenolic and ginger hydrolysed phenolic divisions showed free radical scavenging, inhibition of lipid peroxidation, protection of DNA and diminishing power abilities indicating strong antioxidant properties. Ghasemzadeh et al [46] reported that young rhizome of Z. officinale had higher content of flavonoids with high antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%